Influence of nitrogen source on ruminal pH, ammonia production and protein synthesis - Harbers, L.H.; Richardson, D.; Abe, R.K. (Kansas Agricultural Experiment Station, 2011)
Previous reports from this station indicate little advantage in feeding combined sources of protein (soybean meal and cottonseed meal) to beef cattle. The results were obtained by determining total nitrogen and protein nitrogen in the rumen of fistulated steers at six hours after feeding. By this technique, data that express the ability of the microorganisms to convert nitrogen to bacterial protein may be rapidly determined. Bacterial protein has high biological value; it is, thus, important that maximum conversion be obtained from nitrogen sources of less biological value. Factors that influence conversion can be carefully controlled using fistulated animals. Once optimum rations are formulated under such conditions of rapid screening , costly feeding trials can be minimized.
Keywords: Beef; Rumen pH; Protein synthesis; Steers